2013
DOI: 10.1037/a0034194
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric Bayesian framework for constructing flexible feature representations.

Abstract: Representations are a key explanatory device used by cognitive psychologists to account for human behavior. Understanding the effects of context and experience on the representations people use is essential, because if two people encode the same stimulus using different representations, their response to that stimulus may be different. We present a computational framework that can be used to define models that flexibly construct feature representations (where by a feature we mean a part of the image of an obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 110 publications
2
28
0
Order By: Relevance
“…Although counter-intuitive from the broader perceptual similarity literature, previous behavioral studies with infants and adults on feature correlation predict that intra-item feature similarity should facilitate categorization (e.g., Austerweil & Griffiths, 2011; 2013). Feature correlation studies have shown that objects with correlated features (e.g., bananas tend to be yellow and have a crescent shape) rather than uncorrelated features (e.g., jelly beans come in many colors) enable more robust representations of multi-part objects and categories.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Although counter-intuitive from the broader perceptual similarity literature, previous behavioral studies with infants and adults on feature correlation predict that intra-item feature similarity should facilitate categorization (e.g., Austerweil & Griffiths, 2011; 2013). Feature correlation studies have shown that objects with correlated features (e.g., bananas tend to be yellow and have a crescent shape) rather than uncorrelated features (e.g., jelly beans come in many colors) enable more robust representations of multi-part objects and categories.…”
mentioning
confidence: 87%
“…Feature correlation studies have shown that objects with correlated features (e.g., bananas tend to be yellow and have a crescent shape) rather than uncorrelated features (e.g., jelly beans come in many colors) enable more robust representations of multi-part objects and categories. Having stronger individual object representations due to consistent feature correlations aids categorization of these objects, because the features determining category diagnosticity are more reliable and thus less corrupted by noise (Austerweil & Griffiths, 2011; 2013; Goldstone, 2000; Younger & Cohen, 1986). Consistent feature correlations lead to narrower generalization based on specific features of existing category members, suggesting a tighter category boundary compared to that of uncorrelated features.…”
mentioning
confidence: 99%
“…The parameter l plays the same role as a, controlling how the number of latent causes grows as more customers enter, and hence the 'complexity' of the model. Soto and colleagues used the Indian buffet process in their latent-cause model of compound conditioning [13], and it has also been used in models of perceptual feature learning [58][59][60].…”
Section: Understanding the Effects Of Different Extinction Proceduresmentioning
confidence: 98%
“…This is consistent with the hypothesis that conjunctive training leads to unitization of the set of diagnostic line segments. Furthermore, subsequently presented objects tend to be interpreted in terms of these unitized components (Austerweil & Griffiths, 2013). Goldstone, Rogosky, Pevtzow, and Blair (2005) report a study in which participants first learned to categorize objects on the basis of particular sets of line segments.…”
Section: Introductionmentioning
confidence: 99%